European basic laparoscopic urological skills: a feasibility study in a setting for robot-assisted surgery - Liakos, Nikolaos; Janssen, Martin; Moritz, Rudolf; Kayaci-Güner, Özlem; Bründl, Johannes; Özkan, Arif; Ubrig, Burkhard; Siemer, Stefan; Gratzke, Christian; Wagner, Christian (Frontiers in Surgery, 2025)
IntroductionSince the introduction of laparoscopy, a variety of training sets and tasks have been introduced for surgical education of minimally-invasive surgery. The implementation of the European Basic Laparoscopic Urological Skills into the training and education program of future laparoscopic surgeons created a new era and provided a standardized approach for urological surgical training. However, these tasks have not yet been evaluated in a setting of robot-assisted surgery. The aim of this study is to evaluate the feasibility of the implementation of the four E-BLUS tasks into training modules of robot-assisted surgery.MethodsA cohort of 31 robotic surgeons (group A: experienced, group B: novices) performed these tasks in two different institutions by using the latest generation of robotic surgical platforms. Time performance and failure rate were assessed and statistically analyzed.ResultsThe groups demonstrated a statistically significant difference regarding time performance in half of the tasks involving fine surgical skills (cutting and knotting, p = 0.01 and p = 0.02, respectively) but no significant difference in tasks involving manual ambidexterity (p = 0.14 and 0.12, respectively). A low failure rate during the attempts of the group of novice robotic surgeons could be observed.DiscussionThe use of the E-BLUS tasks in a training setting of robot-assisted surgery is feasible and can lead to the development of surgical skills needed during robot-assisted surgical procedures. It is a relatively low-cost dry lab option for the introduction of novice robotic surgeons.